Differential Modulation of IgT and IgM upon Parasitic, Bacterial, Viral, and Dietary Challenges in a Perciform Fish - Piazzon, Maria C.; Galindo-Villegas, Jorge; Pereiro, Patricia; Estensoro, Itziar; Calduch-Giner, Josep A.; Gómez-Casado, Eduardo; Novoa, Beatriz; Mulero, Victoriano; Sitjà-Bobadilla, Ariadna; Pérez-Sánchez, Jaume (Frontiers in Immunology, 2016)
Three different immunoglobulin isotypes can be found in teleost fish, IgM, IgD and the teleost specific IgT. IgM is considered to have a systemic activity and IgT is attributed a mucosal role, similar to mammalian IgA. In this study the complete sequence of gilthead sea bream IgM and IgT in their membrane (m) and soluble (s) forms are described for the first time in a perciform fish. Their constitutive gene expression is analyzed in different tissues, and their regulation upon viral, bacterial, parasitic, mucosal vaccination and dietary challenges are studied. Gilthead sea bream IgM and IgT have the prototypical structure when compared to other fish immunoglobulins. The constitutive expression of sIgM was the highest overall in all tissues, whereas mIgT expression was highest in mucosal tissues, such as gills and intestine. IgM and IgT were differentially regulated upon infection. IgT was highly up-regulated locally upon infection with the intestinal parasite Enteromyxum leei, or systemically after Nodavirus infection. Long term intestinal parasitic infections increased the serum titer of both isotypes. Mucosal vaccination against Photobacterium damselae subsp. piscicida finely regulated the immunoglobulin response inducing a systemic increase of IgM titers in serum and a local IgT response in skin mucus when animals were exposed to the pathogen by bath challenge. Interestingly, plant-based diets inhibit IgT up-regulation upon intestinal parasitic challenge, which was related to a worse disease outcome. All these results corroborate the mucosal role of IgT and emphasize the importance of a finely tuned regulation of immunoglobulin isotypes upon infection, which could be of special interest in vaccination studies.